2022
DOI: 10.1037/emo0000753
|View full text |Cite
|
Sign up to set email alerts
|

Emodiversity, health, and well-being in the Midlife in the United States (MIDUS) daily diary study.

Abstract: Emodiversity, or the variety and relative abundance of emotions experienced, provides a metric that can be used to understand emotional experience and its relation to well-being above and beyond average levels of positive and negative affect. Past research has found that more diverse emotional experiences, both positive and negative, are related to better mental and physical health outcomes. The present research aimed to test the relationship between positive and negative emodiversity across the span of 8 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…In contrast, the ER diversity index captures individual differences in ER repertoire using one index that is readily computed using the formula presented and thus may have broader accessibility and utility for researchers. Our findings also parallel the findings of a study that examined the diversity in emotional experiences using the emodiversity index (Quoidbach et al, 2014), in which higher positive emodiversity and lower negative emodiversity were associated with fewer depressive symptoms (Urban-Wojcik et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, the ER diversity index captures individual differences in ER repertoire using one index that is readily computed using the formula presented and thus may have broader accessibility and utility for researchers. Our findings also parallel the findings of a study that examined the diversity in emotional experiences using the emodiversity index (Quoidbach et al, 2014), in which higher positive emodiversity and lower negative emodiversity were associated with fewer depressive symptoms (Urban-Wojcik et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…Our findings showed that positive and negative emodiversity were associated with distinct effects. It partly corroborates past studies showing the validity of positively and negatively valenced emodiversity indices (Ong et al., 2018; Urban‐Wojcik et al., 2020). Some studies have used global emodiversity metrics, accounting for the diversity of emotional experiences regardless of valence.…”
Section: Discussionsupporting
confidence: 90%
“…This means that the threshold for individuals with a history of emotional abuse to experience negative emotions may be lower. Higher negative affect emodiversity has also been implicated in depression and anxiety (Urban-Wojcik et al, 2022;Werner-Seidler et al, 2020). There have been some controversies about the measurement of emodiversity and its associations with mental health functioning (Brown & Coyne, 2017), which we discuss in the limitations section.…”
Section: Emotional Abusementioning
confidence: 99%